High strain rate thermoplastic demolding of metallic glasses. (October 2016) - Hasan, Molla; Kumar, Golden
Abstract: Silicon templates are ideal for thermoplastic patterning of metallic glasses but their thermal expansion mismatch prevents demolding without chemical etching. Besides limiting the template life, chemical exposure alters the surface chemistry and properties of metallic glasses. To overcome these issues, we develop thermoplastic demolding which enables template reusability and fabrication of pristine metallic glass structures. Chemical-free demolding allows decoupling of topographic and compositional effects on properties of metallic glasses. We show that mechanically and chemically demolded samples exhibit distinct wetting behavior despite similar topography. The versatility of demolding technique is demonstrated for structures of different shapes and metallic glass formers. Graphical abstract: